Standard reference values of the upper body posture in healthy young female adults in Germany: an observational study - Daniela Ohlendorf; Charlotte Doerry; Vanessa Fisch; Sebastian Schamberger; Gerhard Oremek; Hanns Ackermann; Johannes Schulze (BMJ Open)
Objective Classifications of posture deviations are only possible compared with standard values. However, standard values have been published for healthy male adults but not for female adults.Design Observational study.Setting Institute of Occupational Medicine, Social Medicine and Environmental Medicine, Goethe-University Frankfurt/Main.Participants 106healthy female volunteers (21–30 years old; 25.1±2.7 years) were included. Their body weight ranged from 46 to 106 kg (60.3±7.9 kg), the heights from 1.53 to 1.82 m (1.69±0.06 m) and the body mass index from 16.9 kg/m² to 37.6 kg/m² (21.1±2.6 kg/m²).Outcome measures A three-dimensional back scan was performed to measure the upper back posture in habitual standing. The tolerance ranges and CI were calculated. Group differences were tested by the Wilcoxon Mann-Whitney U test.Results In normal posture, the spinal column was marginally twisted to the left, and the vertebrae were marginally rotated to the right. The kyphosis angle is larger than the lumbar angle. Consequently, a more kyphotic posture is observed in the sagittal plane. The habitual posture is slightly scoliotic with a rotational component (scapular depression right, right scapula marginally more dorsally, high state of pelvic right, iliac right further rotated anteriorly).Conclusions Healthy young women have an almost ideally balanced posture with minimal ventral body inclination and a marginal scoliotic deviation. Compared with young males, women show only marginal differences in the upper body posture. These values allow a comparison to other studies, both for control and patient data, and may serve as guideline in both clinical practice and scientific studies.